Methane production and emission in surface and subsurface rice soils and their blends - Mitra S; Majumdar D; Wassmann, Reiner (Elsevier, 2012)
Methane (CH4) production and emission from three rice-growing soils (Luisiana, Maahas and Pila) of Luzon Island in the Philippines were estimated by incubation and pot culture studies, respectively, to understand their interrelationship. Topsoil (0 20 cm depth) and subsoil (30 50 cm depth) were used for the study along with their blend (1:1) for generating a gradient in soil properties, which allowed evaluating the importance of organic carbon content in regulating CH4 production in both layers of soil. For all the three soil samples, total CH4 production showed a decreasing trend in the order Topsoil > 1Topsoil:1Subsoil > Subsoil. Inoculation by non-sterilized soil suspension in sterilized soils triggered higher CH4 production. It was observed that with the addition of external organic substrates like rice straw, even subsoil produced appreciable amount of CH4. Methane emission was also studied from the same soils cultivated with a rice seedling (IR-72) grown in pots. Temporal pattern of CH4 emission deviated from temporal pattern of its production, i.e. emission patterns either showed a certain time lag (Luisiana and Pila soil) or no significant correlation to the CH4 production (Maahas soil). Methane production and emission rates recorded in this study yielded significant relationship.